Income and Population Growth - Markus Brückner; Hannes Schwandt (Institute for the Study of Labor (IZA), 2013)
Do populations grow as countries become richer? In this paper we estimate the effects on population growth of shocks to national income that are plausibly exogenous and unlikely to be driven by technological change. For a panel of over 139 countries spanning the period 1960-2007 we interact changes in international oil prices with countries' average net oil export shares in GDP. Controlling for country and time fixed effects, we find that this measure of oil price induced income growth is positively associated with population growth. The IV estimates indicate that a one percentage point increase in GDP per capita growth over a ten year period increases countries' population growth by around 0.1 percentage points. Further, we find that this population effect results from both a positive effect on fertility and a negative effect on infant and child mortality.
Keywords: O1; Q56; 330; economic development; population growth